2006
DOI: 10.1016/j.jcrs.2006.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the corneal surface and the anterior segment of the cornea: An Asian perspective

Abstract: There was a close relationship between the various corneal parameters, which is significant in refractive surgery and intraocular lens calculation and design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 23 publications
2
15
1
Order By: Relevance
“…17,18 Therefore, the steeper posterior corneal surface in Chinese eyes in our study might be a manifestation of this ocular dimensional difference because there is a close geometric relationship between corneal curvatures, corneal diameter, and corneal vault. 27 We also found that there was no difference in anterior corneal curvature and corneal thickness between Chinese eyes and German eyes. Our results are compatible with those in previous studies.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…17,18 Therefore, the steeper posterior corneal surface in Chinese eyes in our study might be a manifestation of this ocular dimensional difference because there is a close geometric relationship between corneal curvatures, corneal diameter, and corneal vault. 27 We also found that there was no difference in anterior corneal curvature and corneal thickness between Chinese eyes and German eyes. Our results are compatible with those in previous studies.…”
Section: Discussionsupporting
confidence: 47%
“…The latter can be solved by optimization of IOL power calculation formulas, especially the Haigis formula, which uses 3 coefficients to optimize the ELP prediction algorithm. 19 Several studies of IOL power calculation after corneal refractive surgery in Asian eyes have been published 6,11,[25][26][27] ; however, to date, a simplified method for corneal power estimation has not been evaluated in Asian eyes specifically. Therefore, subsequent research was performed based on our previous study.…”
Section: Discussionmentioning
confidence: 99%
“…12 We also reported a population study of 724 eyes measured with slit-scan topography. 13 Table 1 summarizes the findings in these studies.…”
Section: Resultsmentioning
confidence: 99%
“…12 We also reported a population study of 724 eyes measured with slit-scan topography. 13 Table 1 summarizes the findings in these studies.In this study, we calculated and tested the true keratometric index in a large population based on the actual measurement of the anterior corneal curvature …”
mentioning
confidence: 99%
“…Several commercial imaging modalities are capable of providing shape information for the ocular surface. These devices include slit scanning topography, 8 ultrasound biomicroscopy, 9 Scheimpflug imaging, 10,11 and placido ring-based systems. 12 However, these methods are either limited to evaluating only the central cornea or just providing images with low sampling density due to insufficient acquisition speed.…”
Section: Introductionmentioning
confidence: 99%